(1400) lectures on: Cobol programming language-Part 1 : Essential Cobol-Part 1 : Essential Cobol محاضرة حول: لغة برمجة كوبول - الجزء 1: أساسيات كوبول - El-daoushy, Abdalla (2018)

(untitled)
These lectures deal with the cobol language, the common business oriented language. A language designed for use in business applications. Cobol is in fact the most widely used language in computer world today. It is commercial programming language.